Self-Adjointness, Symmetries, and Conservation Laws for a Class of Wave Equations Incorporating Dissipation. (26th May 2013) - Wang, Yang; Wei, Long
Abstract : In this work, we study the nonlinear self-adjointness and conservation laws for a class of wave equations with a dissipative source. We show that the equations are nonlinear self-adjoint. As a result, from the general theorem on conservation laws proved by Ibragimov and the symmetry generators, we find some conservation laws for this kind of equations.